Exploring the challenges and coping strategies of rural high schools in resuming to in-person classes - Petiluna, F Roylan Hope C.; Naparan, Genesis B. (Edukasiana: Jurnal Inovasi Pendidikan, 2024)
This study intends to explore the challenges and coping strategies of selected public rural high schools in transitioning from modular to in-person classes. It utilizes a qualitative-case study design gathering primary data by interviewing school heads, ancillary coordinators, teachers, and parents from 3 public high schools in the rural districts of Pagadian City. Coding was the strategy used to analyze the data gathered. Analysis reveals that amidst the implementation of full in-person classes, schools experienced challenges in adapting to the new normal, managing misbehavior, academic unpreparedness, mental health concerns, maintaining health and safety standards, and sustaining school operations. Consequently, schools applied measures to address such challenges by applying systematic response, resourcefulness, effective communication, sustaining productivity, and creating an encouraging environment. Hence, recommendations to further address challenges were discussed. The primary contribution of this study lies in providing a deeper understanding of the challenges and coping strategies faced by rural high schools in transitioning to the "new normal" of education. This study contributes to providing a deeper understanding of the challenges and coping strategies faced by rural high schools in transitioning to the "new normal" of education.